Aryl hydrocarbon receptor and IL-13 signaling crosstalk in human keratinocytes and atopic dermatitis - Proper, Steven P.; Dwyer, Alexander T.; Appiagyei, Andrews; Felton, Jennifer M.; Ben-Baruch Morgenstern, Netali; Marlman, Justin M.; Kotliar, Michael; Barski, Artem; Troutman, Ty D.; Rothenberg, Marc E.; Mersha, Tesfaye B.; Azouz, Nurit P. (Frontiers in Allergy, 2024)
Introduction Atopic dermatitis (AD) is an allergic skin disease mediated by skin barrier impairment and IL-13-driven immune response. Activation of the aryl hydrocarbon receptor (AHR) has shown promise in early clinical trials for AD; however, the mechanism by which AHR partially ameliorates AD is not well known. Methods Gene expression data from human biopsies were analyzed, and compared to gene expression from RNA-sequencing in our in-vitro HaCaT cell model system. Western blot, ELISA qRT-PCR were used to further explore the relationship between AHR and IL-13 signaling in HaCaT cells. Results The AHR target gene CYP1A1 was decreased in lesional skin compared with healthy control skin (p = 4.30 × 10−9). Single-cell RNA sequencing (scRNAseq) demonstrated increased AHR expression (p < 1.0 × 10−4) and decreased CYP1A1 expression in lesional AD keratinocytes compared with healthy control keratinocytes (p < 0.001). Activation of AHR by AHR agonists in HaCaT cells reversed IL-13-dependent gene expression of several key genes in AD pathogenesis, most notably the eosinophil chemoattractant CCL26 (eotaxin-3). Differentially expressed genes in keratinocytes of patients with AD substantially overlapped with genes regulated by AHR agonists from HaCaT cells by RNAseq, but in reverse direction. Mechanistically, there was evidence for direct transcriptional effects of AHR; AHR binding motifs were identified in the differentially expressed genes from lesional AD keratinocytes compared to control keratinocytes, and AHR activation did not modify IL-13-dependent signal transducer and activator of transcription 6 (STAT6) translocation to the nucleus. Discussion Together, these data suggest that the AHR pathway is dysregulated in AD and that AHR modulates IL-13 downstream signaling in keratinocytes through genome-wide, transcriptional regulatory effects.